3-(3-Methylphenoxy)-1,5-dihydro-2,4,3-benzodioxaphosphepin-3-one - Krishna, J. Radha; Krishnaiah, M.; Babu, M. F. Stephen; Reddy, C. Suresh; Puranik, Vedavati G. (Acta Crystallographica Section E-Structure Reports Online, 2007)
In the title compound, C15H15O4P, the seven-membered phosphepine ring exhibits a twist-chair conformation, with the phosphoryl O atom in an equatorial and the methylphenoxy group in an axial position. The crystal structure is stabilized by both intra- and intermolecular C-H center dot center dot center dot O hydrogen bonds.